STUDENTS’ COMMON ERRORS IN TRANSLATING PHRASAL VERBS: A CASE OF STUDENTS IN ISLAMIC EDUCATION PROGRAM - Ghufron, M. Ali (IKIP Siliwangi, 2022)
The objectives of this study were to determine (1) the types of errors students made when translating phrasal verbs, (2) the frequency with which students made errors when translating phrasal verbs, and (3) the reasons of students' errors when translating phrasal verbs. The study used a qualitative case study approach and was conducted with second-semester students enrolled in the Islamic Education Program at a State Institute for Islamic Studies (Institut Agama Islam Negeri) in Central Java, Indonesia. The data sources were documents generated as a consequence of the exam and interview with the students. The author gathered data by doing an error analysis of students' test scores as provided by their lecturer. The obtained data were examined in steps that included collecting data, detecting mistakes, categorizing errors according to their categories, summarizing the errors for each category, and assessing the students' errors. Additionally, to ascertain the causes of students' mistakes, the researcher performed an interview with students who were purposefully chosen. According to the researcher's findings, students made two sorts of errors while translating phrasal verbs: errors in propositional meaning, which are incorrect alternate meanings for words, and errors in expressive meaning, which are incorrect translations of idiomatic expressions. Meanwhile, the interview findings indicated that the reasons for students' errors include a lack of understanding of what a phrasal verb is, a dislike for English, a lack of vocabularies, and a tendency to be lazy about learning more about English because they believe it is difficult.